2001
DOI: 10.1046/j.1365-2958.2001.02676.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient uptake of Yersinia pseudotuberculosis via integrin receptors involves a Rac1–Arp 2/3 pathway that bypasses N‐WASP function

Abstract: Efficient uptake of Yersinia pseudotuberculosis into cultured mammalian cells is the result of high‐affinity binding of invasin to β1 chain integrins. We demonstrate here that uptake requires Rac1 and Arp 2/3 function. Bacterial uptake was stimulated by GTPγS, but was inhibited in mammalian cells transfected with the interfering Rac1‐N17 derivative. Rac1 was found to be activated in response to integrin engagement by invasin, whereas Rac1 and Arp 2/3 were found to be intensely localized around phagosomes beari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 44 publications
(81 reference statements)
4
58
1
Order By: Relevance
“…Nevertheless, they provide an explanation for why YopO has an effect on NADPH oxidase activation, a process that is Rac2-dependent (35). Furthermore, our work supports the data that suggest Yersinia target ␤ 1 -integrin-mediated uptake by phagocytes, a process shown to require Rac and not Rho (36).…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, they provide an explanation for why YopO has an effect on NADPH oxidase activation, a process that is Rac2-dependent (35). Furthermore, our work supports the data that suggest Yersinia target ␤ 1 -integrin-mediated uptake by phagocytes, a process shown to require Rac and not Rho (36).…”
Section: Discussionsupporting
confidence: 85%
“…In Y. pseudotuberculosis, it has been demonstrated that the nature of the adhesin and the specific signaling cascade that it triggers in host cells are critical in determining the efficiency of Yop delivery (38). It has been proposed that integrin-mediated signaling in host cells following Y. pseudotuberculosis invasin-integrin interaction re-sults in a series of events leading to efficient YopB/YopD pore formation in host cells and subsequent T3SS-mediated Yop delivery (1,2,38,62,66). We hypothesize that since Y. pestis lacks invasin, Ail may mediate a receptor interaction that initiates a similar series of events leading to pore formation and Yop delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Invasin tightly binds to, and causes clustering of, β1 integrins on the cell surface, thereby leading to rapid activation of Rac1 and the induction of membrane protrusions in host cells. Rac1 activity is required for membrane ruffling initiated by integrin-invasin interactions and for uptake of Yersinia bacteria by host cells (Alrutz et al, 2001). The FAK-Src complex might transmit signaling from β1 integrins to Rac1 GTP loading; this is supported by the findings that invasin-mediated bacterial uptake is impaired in FAK -/-cells, and that the expression of a FAK Y397F mutant that cannot bind to SFKs does not restore this defect (Alrutz and Isberg, 1998;Bruce-Staskal et al, 2002).…”
Section: Phagocytosis and Engulfmentmentioning
confidence: 99%